Legal Analysis of LGBT Behavior Among TNI Soldiers: Implementation of Regulations and Their Impact on Military Discipline - Sorna Nauli Nasution; Hambali Yusuf; Erli Salia (Jurnal Ilmiah Galuh Justisi, 2025)
This study aims to analyze the criminal liability of TNI soldiers involved in Lesbian, Gay, Bisexual, and Transgender (LGBT) behavior in the context of Indonesian military law, focusing on the implementation of regulations at the Palembang I-04 Military Court. Although there is no explicit provision in the Criminal Code (KUHP) that prohibits LGBT behavior, conservative social norms in Indonesia and strict TNI internal regulations on soldier discipline can lead to violations of the ethics and morals accepted by the military institution. This study uses a qualitative approach by analyzing applicable regulations, military justice practices, and the impact of disciplinary policies on TNI soldiers involved in LGBT behavior. The results of the study indicate that TNI soldiers involved in LGBT behavior are at risk of being subject to disciplinary sanctions based on Government Regulation No. 39 of 2010 concerning Military Discipline and TNI Regulation No. 23 of 2010 concerning Mental and Ethical Development of TNI Soldiers. These sanctions can include dishonorable discharge or demotion, although there is no explicit prohibition in general criminal law. In addition, the Palembang I-04 Military Court plays a role in trying disciplinary violations that occur, by assessing whether the LGBT behavior tarnishes the image of the TNI or is contrary to the norms held by the institution. This study provides insight into the application of military law to LGBT issues in a conservative social context, as well as the importance of consistent and fair discipline enforcement in dealing with social developments in Indonesia. In addition, this study also offers recommendations for TNI internal policies to be more responsive to issues of sexual diversity, along with efforts to maintain the integrity and credibility of the institution.